The Effect of Using Visual Realization Exercises in Learning Compound Rushes by Foil (Journal of the College of Basic Education, 2022)
Fencing is one of the sports that needs a high and accurate focus, information which the learner focus on, and does not grasp without the safety of the organs of sense and the safety of ability of the learner to realize when the player can realize the weak points of his foe, he can take the touches and win the game. Here, the benefit of the research appears by trying to achieve active and fruitful learning by using visual realization exercises in learning the compound offensive skills by foil. throughout the concern of the researcher as one of the interested persons in Fencing and one of its practitioners, he observed that there are many of teachers do not confirm on using visual exercises in teaching that give the learner an ability to learn by increasing the beauty of the exercise and doing the skills in more suspension from the learner. The problem of the research is in the weak use of visual realization exercises of learning compound offensive skills by Foil. The process of the research is represented by the empirical process and a sample of the research, which is represented by the students of forth year/college of physical education and sport science/ university of Al-Qadisiya 2015-2016, which has 34 students divided into two groups (regulator(17),empirical(17)). Homogeneity is done for them in the averages of growing, also the parity in the prior test. Then the scouting experiment is done and followed by prior tests and then the related exercises of the regulator group, and visual realization exercises were applied on the educational units of the empirical group. Then the followed tests are done and SPSS is used to get the results. The analyzing and discussion of the prior and following tests of the compound offensive skills by Foil are presented and the researcher found that:The prepared exercises by the researcher(visual realization exercises) are affective in learning the compound offensive skills by Foil.It is appeared the superiority the individuals of the empirical group on the individuals of the regulator group in learning the compound offensive skills by Foil.